SCIENTIFIC STUDY ON RAKTA DHATU AND ITS RELATED DISORDER AND EFFECT OF VARNYA MAHAKASHAYA GHANVATI AND CHANDRA PRABHA LEPA IN THE MANAGEMENT OF YUVAN PIDIKA (ACNE VULGARIS) (International Journal of Ayurveda and Pharma Research, 2015)
Due to increased competition of earning prosperity in today era human adopted not only lifestyle but also food habits of western culture which is chiefly responsible to derangement in their physiology and responsible to number of skin disorder like Yuvan pidika (acne vulgaris). In Ayurveda vitiation of Vata, Kapha and Rakta are etiological factor that give rise to Yuvan pidika. That is why there is a need of such treatment that contains Vata kapha shamaka and Raktasodhaka property. For this Varnya Mahakashaya Ghanvati and Chandra Prabha lepa were selected for the study on 30 registered patients. Both of these were formulated compound. Varnya Mahakashaya Ghanvati was advocated to patient in a dose of 800 mg twice daily for 60 days while Chandra Prabha lepa was locally applied by making paste with Gulab jala. This study shows highly significant result to ameliorate the symptom of Yuvan pidika especially on Vata dosha pidika as well as Kapha dosha pidika. Both these drugs proved their efficacy to manage Yuvan pidika by making homeostasis of Vata, Kapha and Rakta.